The Call of Jihad in Adding the Adhan Narrative to the Perspective of Islamic Law - Kasjim Salenda; Ahmad Fauzan; Muhammad Nafi (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
At the end of the year 2020, social media was in an uproar over the addition of the jihad narrative to the call to prayer, which included an invitation to jihad. Certain elements of a small portion of the Muslim population exhaled the issue. This study aims to examine the position of the call to prayer in Islamic law and the evaluation of Islamic law regarding the call to jihad in the form of the call to prayer. This type of research employs a normative methodology. In the form of the addition of the call to prayer narration, primary data sources were acquired from a variety of social media posts pertaining to challenges requiring jihad. Additional primary sources acquired from books and periodicals. The results of this study indicate that the call to prayer has been a part of Islamic law from the time of the Prophet Muhammad PBUH, serving as a reminder and a call to congregational prayer. The call for jihad in the form of the call to prayer is not included as the call to prayer, may not be called as a call to prayer, and is called during prayer times and in a location that can cause people to panic, as the call for jihad in the form of the call to prayer has never been carried out and exemplified by the Messenger of Allah. By adding a narration to the call to prayer, Muslims should not be inflamed by jihad appeals. However, one cannot overlook the phenomena of the call to jihad that has gone viral because to the actions of specific individuals. Obviously, the government and related bureaucracy wish to take resolute measures so as not to disrupt public order as a consequence.